Urgensi Pendidikan Multikultural dalam Pengembangan Karakter di Era Society 5.0 pada Perguruan Tinggi - Muhammad Dwi Toriyono; Annas Ribab Sibilana; Bagus Wahyu Setyawan (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2022)
Along with the times, many students, especially in universities, have no character as students. Politeness, manners, and morals have begun to be underestimated. So, it is important to apply multicultural education in university as an alternative and solution to make students with the character through multicultural values. The research method used in this study is a descriptive analysis by collecting various data and sources, then analyzing and systematically describing the urgency of multicultural education in character development in the era of society 5.0 at universities. The study's results found that students' character in university began to decline. Multicultural cultural values ​​have been abandoned. Many students have ignored etiquette, manners, and behavior, especially lecturers as teachers or educators. So, through multicultural education, it is expected to contribute in terms of character building. It is implemented by providing good examples such as the habituation of respect for others, mutual respect, and advice if there is bad behavior.